Kajian fitokimia dan aktiviti biologi ke atas piper umbellatum - Che Haslinaida, Che Hassan (Universiti Malaysia Sarawak (UNIMAS), 2005)
Phytochemical and biological studies have been carried out on the stem of Pier umbellatum. The extracts were subjected to thin layer chromatography, column chromatography and preparative thin layer chromatography in order to isolate and purify pure compounds. Three semi pure compounds were isolated, EA 07 (i), EA 08 (ii) and EA 10 (iii) with Rf values of 0.72, 0.88 and 0.54 in hexane-ethyl asetate (5: 3) respectively. In the toxicity test, most of the. fractions and crude extracts indicated a low toxicity on the larvae Artemia salina. Only fraction EA07 showed LD50 at 40 , ug/mL. Fractions EA08 and EA10 gave LD50 of 55 pg/mL and 100 ug/mL respectively.